Innovation and preservation of traditional values: development of distinctive nusantara batik motifs in women's swimwear design using digital printing techniques - Wesnina Wesnina; Yoga Matin Albar (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
This research examines the application of contemporary Nusantara batik motifs to women's swimwear using digital printing techniques, with a specific focus on measuring product dimensions, design elements, and design principles. The study employed a mixed-methods approach combining quantitative surveys with expert panel assessments. Data were collected from five design and textile experts and 100 female respondents aged 18-25 years through validated instruments measuring three key variables: product dimensions (functionality, aesthetics, comfort), design elements (form, color, texture), and design principles (balance, harmony, proportion). Statistical analysis using PLS-SEM revealed that both product dimensions (β=0.482, t=7.171, p<0.001) and design elements (β=0.424, t=6.327, p<0.001) significantly influence the acceptance of design principles in batik-inspired swimwear. The highest consumer acceptance was for the "appearance of batik motifs on swimwear" (mean 4.27) and "harmony of batik colors in swimwear" (mean 4.22). These findings demonstrate that traditional Indonesian motifs can be successfully adapted to contemporary functional garments while preserving cultural significance. This research contributes to the growing field of culturally-inspired fashion innovation by providing a methodological framework for evaluating the integration of traditional motifs in modern applications and offers practical insights for designers and manufacturers seeking to develop culturally distinctive products for younger consumers.